A strategy for fabricating anisotropic SI3N4 ceramics with controllable mechanical and thermal properties. Issue 1 (9th September 2020) - Zhao, Zhe; Lu, Xugao; Zhou, Guoxiang; Yang, Yitian; Lin, Kunpeng; Yang, Zhihua; Jia, Dechang; Zhou, Yu
Abstract: Heat dissipation material with programmable anisotropic property is very challenging, yet can realize the controllable thermal diffusion for heating device. In this work, anisotropic Si3 N4 ceramics with oriented grains are prepared to adjust and improve the mechanical and thermal properties under the applied stress field by rolling film forming technology. Through the design of the sintering aids in the process of liquid‐phase sintering, the orientation degree of the Si3 N4 grains is programmable as well as the mechanical property and the thermal property of the Si3 N4 ceramics. As a consequence, the obtained Si3 N4 ceramics show significant anisotropy in mechanical properties and thermal conductivity. The typical fracture toughness and thermal conductivity along the grain orientation direction are 10.6 MPa⋅m 1/2 and 45.45 W/(m⋅K) while they are 4.5 MPa⋅m 1/2 and 66.42 W/(m⋅K) in the direction perpendicular to the oriented grain, respectively. This grain orientation method paves the way for the thermal performance design and the production of programmable heat dissipation material.